Penentuan Rute dan Pengelolaan Persediaan dengan Mempertimbangkan Jumlah Permintaan Stokastik dan Jendela Waktu - Achmad, Andi Muhammad Fiqri; Irfan Rusydi Triyanto (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
One problem with stochastic characteristics is the drug distribution process. Drug demand originates from pharmacies, with the quantity requested varying each time a request is sent. This can be caused by several factors, one of which is that people's illnesses also vary and are not always the same. Due to this fluctuating demand from pharmacies, drug distributors must also provide larger quantities of drugs in their warehouses as safety stock. This study aims to develop a mathematical model for determining distribution vehicle routes and inventory management by considering uncertain demand and the presence of time windows. The developed mathematical model is in the form of a MILP. The data used is entirely synthetic and randomly generated. Data processing is carried out with several scenarios, by measuring the objective function value and computation time. The data processing results have produced a global optimal solution for 15 retailers and 5 different Beta value scenarios. The objective function value and computation time will increase with the increase in the number of retailers/pharmacies.